Causation and explanation - Psillos, Stathis, 1965- (Central problems of philosophy (Montréal, Québec), 2002)
"Stathis Psillos divides his account into three sections: causation, laws of nature, and explanation. He begins the causation section with Hume's classic "reductive" account and then focuses on the subsequent division between Humean and non-Humean accounts, examining topics such as regularities and singular causation, causation and counterfactuals, and causation and mechanism. In the section on laws of nature, Psillos considers both the regularity view of laws and laws as relations among universals as well as alternative approaches to laws. In the final section on explanation he examines in detail the issues arising from deductive-nomological explanation and statistical explanation before considering the explanation of laws and the metaphysics of explanation. Accessible to students of all levels the author provides an excellent introduction to one of the most enduring problems of philosophy.--